Academics’ perceptions of the effects of globalization on Turkish foundation* university policies** - (:unkn) unknown (My University, 2012)
Batılı ülkeler küreselleşmenin olumsuz etkileriyle mücadele ederken, Türkiye gibi batılılaşma yolunda olan, ancak batılı ülkeler tarafından Müslüman bir Asya-Avrupa ülkesi olarak kabul edilen bir ülkede küreselleşmenin batılı ülkelerdekine benzer etkiler doğurup doğurmadığı, son yıllarda akademisyenlerin ve araştırmacıların merak konusu olmuştur. Bu nedenle çalışmada, akademisyenlerin küreselleşme sürecinin yükseköğretim kurumları üzerindeki etkilerini nasıl algıladıklarını incelemek amaçlanmaktadır. Araştırmada nitel veri toplama teknikleri kullanılmıştır. Analizler, Türkiye’deki iki vakıf üniversitesinde görev yapmakta olan 19 akademisyenle yapılan görüşmelere dayanmaktadır. Araştırma sonuçları, küreselleşme sürecinin üniversiteleri hedefler, pazarlama politikaları ve akademisyenlere sağlanan profesyonel gelişim imkânları alanlarında etkilediğini ortaya koymaktadır.

While western countries are coping with the challenges arising from globalization, a key question being asked is whether the same or similar challenges are dominating a country that is trying to become westernized but regarded as a Muslim-European-Asian country. This study, therefore, attempts to explore academics’ perceptions regarding the impact of the globalization process on higher education institutions in a country like Turkey that has a different culture, history, language, and so on, compared to other European communities. Analyses are based on qualitative interviews with 19 academics working at two foundation universities in Turkey. Findings of the study reveal that globalization has affected university policies in the areas of goals, marketing policies and the professional development opportunities provided for academics.
Akademisyenlerin algılamalarına göre küreselleşmenin Türk vakıf üniversite politikaları üzerine etkileri
Keywords: Eğitim, Eğitim Araştırmaları